Features of the geological structure of NASA Perseverance rover landing site on Mars based on the results of frequency-resonance processing of images from spacecrafts - Yakymchuk, M.A.; Korchagin, I.M. (Reports of the National Academy of Sciences of Ukraine, 2021)
The results of experimental studies on the Mars at the local landing site of the NASA Perseverance rover, in the Jezero crater area and on an area in the northern part of the planet are presented. Reconnaissance studies were carried out using the methods of frequency-resonance processing and the interpretation of images of survey sites from spacecrafts in order to study the features of their geological structure. Instrumental measurements showed that the landing site of the rover is located within a volcanic structure, filled with marls. Fragments of siliceous rocks were found on the surface in the landing zone. In a vicinity of the Jezero crater, the instrumental measurements have established (confirmed) the presence in the planet’s cross-section, of 8 types of volcanic structures filled with: 1) salt; 2) limestones; 3) dolomites; 4) marls; 5) siliceous rocks; 6) basalts; 7) ultramafic rocks; 8) kimberlites. Examination of individual areas of the planet confirmed the presence of only 27 chemical elements known on the Earth. Oxygen also belongs to the chemical elements, absent on the Mars. The lack of oxygen in the composition of the Mars indicates that there is no water on the planet, and, therefore, no ice in the Polar Regions. Large volcanic structures filled with salt have been discovered in the area near the north pole of the Mars. The numerous volcanic complexes found on the Mars filled with rocks of various compositions are important arguments in favor of a volcanic model of formation of the planet outer appearance. The research results indicate the fundamental possibility of using the data from remote sensing of planets and satellites of the solar system (images from spacecrafts, landing modules, and telescopes) to study the internal structure of survey objects and the composition of rocks, minerals, and chemical elements, present on them. The frequency— resonance technology of satellite images and the photo images processing can be used to carry out detailed studies on planets and satellites of the solar system in the framework of large scientific projects to study them. The proven mobile technology can also find applications in the selection of rock sampling sites for the rover.